Sosialisasi dan Pelatihan Pemeliharaan Unggas Lokal di Kelompok Wanita Tani Kejora Sawahlunto - Robi Amizar; Wizna Wizna; Mirzah Mirzah; Ade Djulardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
This activity aims to realize a growing livestock business in Kelompok Wanita Tani (KWT) Kejora in Sawahlunto that can generate profits to increase household incomes for KWT Kejora partner groups. The implementation of this activity was carried out in three stages; the first was the delivery of material and distributing questionnaires, the second stage was training and modeling, and the third stage was post-training assistance. The service activities in the form of socialization and training on local poultry farming at the KWT Kejora Sawahlunto have been carried out well. The result of this activity was that this activity was attended by 20 group members and accompanied by field officers from the Food Security, Agriculture, and Fisheries Service of Swahlunto City. Group members generally know about local poultry farming (village chicken) but do not know how to raise chickens properly and do not know the factors that affect the sustainability of the livestock business. Therefore, this group must continue to be accompanied so that the sustainability of the group's business can develop and increase the household income of group members.